Identification and Elucidation of the Protective isomiRs in Lung Cancer Patient Prognosis - Hsieh, Fu-Mei; Lai, Su-Ting; Wu, Ming-Fong; Lin, Chen-Ching (Frontiers in Genetics, 2021)
MicroRNAs (miRNAs) are about 20-22 nucleotides in length, which are well known to participate in the post-transcriptional modification. The mature miRNAs were observed to be varied on 5ʹ or 3ʹ that raise another term — the isoforms of mature miRNAs (isomiRs), which have been proved not the artifacts and discussed widely recently. In our research, we focused on studying the 5’ isomiRs in lung adenocarcinoma (LUAD) in the Cancer Genome Altas (TCGA). We characterized 75 isomiRs significantly associated with better prognosis and 43 isomiRs with poor prognosis. The 75 protective isomiRs can successfully distinguish tumors from normal samples and are expressed differently between patients of early and late stages. We also found most of the protective isomiRs tend to be with downstream shift and up-regulated compared to those with upstream shift, implying a possible selection occurs during cancer development. Among these protective isomiRs, we observed a highly positive and significant correlation, as well as in harmful isomiRs, suggested cooperation within the group. However, between protective and harmful, there’s no such a concordance but conversely more negative correlation, suggesting the possible antagonistic effect between protective and harmful isomiRs. We also identified two isomiRs miR-181a-3p|-3 and miR-181a-3p|2 respectively belong to the harmful and protective group, suggested a bidirectional regulation of their originated archetype—miR-181a-3p. Additionally, we found that the protective isomiRs of miR-21-5p, which is an oncomiR, may be evolved as the tumor suppressors through producing isomiRs to hinder metastasis. In summary, these results displayed the characteristics of the protective isomiRs and their potential for developing the treatment of lung cancer.